Retiree goes for second degree: ex-land officer, 71 pursues ambition to become a lawyer - Zainal, Fatimah (The Star, 2016)
KUALA LUMPUR: After decades of toiling round the dock and raising a family, most retirees would prefer to sit back and relax.